Pharmacogenomics of the Efficacy and Safety of Colchicine in COLCOT. (9th February 2021) - Dubé, Marie-Pierre; Legault, Marc-André; Lemaçon, Audrey; Lemieux Perreault, Louis-Philippe; Fouodjio, René; Waters, David D.; Kouz, Simon; Pinto, Fausto J.; Maggioni, Aldo P.; Diaz, Rafael; Berry, Colin; Koenig, Wolfgang; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The randomized, placebo-controlled COLCOT (Colchicine Cardiovascular Outcomes Trial) has shown the benefits of colchicine 0.5 mg daily to lower the rate of ischemic cardiovascular events in patients with a recent myocardial infarction. Here, we conducted a post hoc pharmacogenomic study of COLCOT with the aim to identify genetic predictors of the efficacy and safety of treatment with colchicine. Methods: There were 1522 participants of European ancestry from the COLCOT trial available for the pharmacogenomic study of COLCOT trial. The pharmacogenomic study's primary cardiovascular end point was defined as for the main trial, as time to first occurrence of cardiovascular death, resuscitated cardiac arrest, myocardial infarction, stroke, or urgent hospitalization for angina requiring coronary revascularization. The safety end point was time to the first report of gastrointestinal events. Patients' DNA was genotyped using the Illumina Global Screening array followed by imputation. We performed a genome-wide association study in colchicine-treated patients. Results: None of the genetic variants passed the genome-wide association study significance threshold for the primary cardiovascular end point conducted in 702 patients in the colchicine arm who were compliant to medication. The genome-wide association study for gastrointestinal events was conducted in all 767 patients in the colchicine arm and found 2 significant association signals, one with lead variant rs6916345 (hazard ratio, 1.89 [95% CI, 1.52–2.35], P =7.41×10 −9 ) in a locus which colocalizes with Crohn disease, and one with lead variant rs74795203 (hazard ratio, 2.51 [95% CI, 1.82–3.47]; P =2.70×10 −8 ), an intronic variant in gene SEPHS1 . The interaction terms between the genetic variants and treatment with colchicine versus placebo were significant. Conclusions: We found 2 genomic regions associated with gastrointestinal events in patients treated with colchicine. Those findings will benefit from replication to confirm that some patients may have genetic predispositions to lower tolerability of treatment with colchicine.